Tissue-type plasminogen activator induces TNF-α-mediated preconditioning of the blood-brain barrier. Issue 4 (April 2022) - Diaz, Ariel; Woo, Yena; Martin-Jimenez, Cynthia; Merino, Paola; Torre, Enrique; Yepes, Manuel
Ischemic tolerance is a phenomenon whereby transient exposure to a non-injurious preconditioning stimulus triggers resistance to a subsequent lethal ischemic insult. Despite the fact that not only neurons but also astrocytes and endothelial cells have a unique response to preconditioning stimuli, current research has been focused mostly on the effect of preconditioning on neuronal death. Thus, it is unclear if the blood-brain barrier (BBB) can be preconditioned independently of an effect on neuronal survival. The release of tissue-type plasminogen activator (tPA) from perivascular astrocytes in response to an ischemic insult increases the permeability of the BBB. In line with these observations, treatment with recombinant tPA increases the permeability of the BBB and genetic deficiency of tPA attenuates the development of post-ischemic edema. Here we show that tPA induces ischemic tolerance in the BBB independently of an effect on neuronal survival. We found that tPA renders the BBB resistant to an ischemic injury by inducing TNF-α-mediated astrocytic activation and increasing the abundance of aquaporin-4-immunoreactive astrocytic end-feet processes in the neurovascular unit. This is a new role for tPA, that does not require plasmin generation, and with potential therapeutic implications for patients with cerebrovascular disease.